2014
DOI: 10.1097/md.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial Giardia Intestinalis

Abstract: The giardiasis is a neglected parasitic disease. The WHO has estimated more than 280 million of human infections each year; however, intraepithelial giardiasis is a rare entity, there are only 5 reports showing invasive giardiasis.A pediatric female patient with chronic abdominal pain, diarrhea, or pasty stools, without fever, was seen in the Gastroenterology and Nutrition Service. The stool studies were negative for pathogens and lactose hydrogen breath test was positive. The presumptive clinical diagnosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Infection with Giardia occurs after ingestion of the environmental cyst stage of the parasite, which upon gastric passage excysts to release two trophozoites into the less acidic and bile-enriched environment of the upper small bowel. Trophozoites adhere to epithelial cells and replicate but typically do not invade the intestinal mucosa or cause ulceration [ 6 , 66 ]. If symptoms develop, onset typically begins after a 6- to 15-day incubation period that oftentimes precedes detection of parasites in stool [ 5 ].…”
Section: Determining How Giardia Causes Diseasementioning
confidence: 99%
“…Infection with Giardia occurs after ingestion of the environmental cyst stage of the parasite, which upon gastric passage excysts to release two trophozoites into the less acidic and bile-enriched environment of the upper small bowel. Trophozoites adhere to epithelial cells and replicate but typically do not invade the intestinal mucosa or cause ulceration [ 6 , 66 ]. If symptoms develop, onset typically begins after a 6- to 15-day incubation period that oftentimes precedes detection of parasites in stool [ 5 ].…”
Section: Determining How Giardia Causes Diseasementioning
confidence: 99%
“…It is also effective against Trichomonas spp., Entamoeba histolytica , Clostridium difficile , Clostridium perfringens , Helicobacter pylori , and Campylobacter jejuni [ 19 ]. It has been shown that NTZ has a similar efficacy for eliminating Giardia when compared to metronidazole, but has fewer adverse effects [ 20 23 ]. To the best of our knowledge, there are no formal studies on the effect of NTZ against clinical infections of Giardia in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The colonization of the gut is followed by alterations in the gut milieu in favor of the parasite. To do so, the protozoon uses different mechanisms [ 37 ]. Non-specific mechanisms involve adhesion to host enteric epithelial cells by mechanical suction force via the ventral suction or adhesive disk and alterations in the zonula occludens tight junctions [ 37 , 38 ].…”
Section: Parasite–host Interactionmentioning
confidence: 99%
“…To do so, the protozoon uses different mechanisms [ 37 ]. Non-specific mechanisms involve adhesion to host enteric epithelial cells by mechanical suction force via the ventral suction or adhesive disk and alterations in the zonula occludens tight junctions [ 37 , 38 ]. The ventral suction disk of Giardia lamblia is a means of attachment to the small intestine to protect the trophozoite from being carried away by enteric peristalsis and gut contents [ 39 ].…”
Section: Parasite–host Interactionmentioning
confidence: 99%